Implementasi Lean Manufacturing Car Body Studi Kasus di PT Inka (Persero) - Raden Denny Herwindo; Udisubakti Ciptomulyono; M. Yusak Anshori (UNUSA Press, 2017)
Means of rail transport in developing countries became major commodities integrated transportation solutions, rail transport is efficient for the number of mass transit. It opens the market potential procurement of railway facilities by PT INKA, both in the domestic market or abroad. As a make to order-based manufacturing started in 2008 with a lot of project exports todeveloping countries, such as Bangladesh, Malaysia and Singapore. PT INKA export market opportunities potentially enough ahead to 2020, but delays in delivery schedule of the train is the main problem is always the case in recent years. Methods of lean manufacturing focuses on identifying and eliminating activities that do not have added value, the first step was the elaboration of a method VSM (value stream mapping) as tools to determine mapping the entire process of production, then weighted 7 waste via a questionnaire and the results of the ranking of waste are translated through the method of RCA (root cause analysis) and then do an analysis matrix mapping tools with value stream analysis tools (VALSAT) and there is a value added value ratio of 60.17% of the 84 activities of production and the total cycle time 29,905 minutes. As a tool to mitigate the improvement of waste carried out the translation of failure mode and effect analysis (FMEA) and of design improvements value stream mapping - future state map can raise the value added ratio to 67.16% consists of 74 processes and production activities 26 795 minutes total cycle time. So this research can increase the productivity and know the activities that do not add value (Non Value Added) in line car body processes and eliminating waste (Waste) as one of the causes of train delays in delivery.